GRAND DESIGN LEMBAGA PEREKONOMIAN NAHDLATUL ULAMA (LPNU) JAWA TIMUR DALAM PEMBERDAYAAN UMKM MELALUI GERAKAN NUCONOMIC - Hajar (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
NU as the largest Islamic organization in the world, one of its functions is to empower in the economic field in order to realize economic development and equity, and provide equal opportunities to enjoy the results of development. The spirit of this movement certainly cannot be separated from the spirit of Nahdlatut Tujjar as one of the embryos of the birth of NU, where this organization was formed one of the goals was to give birth to Muslim entrepreneurs to solve the economic problems felt by the community at that time. In practice, the NU populist economic movement is carried out, among others, through LPNU as an institution that concentrates on the economic field, where the East Java LPNU has specifically formulated a grand design in empowering MSMEs through the NUCONOMIC movement. This article is a study of the NUCONOMIC program as a grand design of the East Java Nahdlatul Ulama Economic Institute (LPNU) in empowering MSMEs which is focused on two main problems: (1) how is the implementation of NUCONOMIC in empowering MSMEs in East Java LPNU? (2) what are the challenges and opportunities for the NUCONOMIC movement of East Java LPNU in empowering MSMEs? This research uses qualitative methods with an ethnographic approach. Data collection techniques are carried out by means of observation, interviews, and documentation. The results of this research show that the grand design of the NUCONOMIC program is carried out with five stage processes, namely: (a) Training; (b) Assistance; (c) Exhibitions; (d) Technology; and (e) Monev.